Strategic Management in the Digital Era: A Bibliometric Analysis of Digital Transformation Trends - Ni Nyoman Sawitri (Siber Nusantara Review & Yayasan Sinergi Inovasi Bersama (SIBER), 2026)
The convergence of strategic management and digital transformation has become a central theme in contemporary business research, yet the intellectual structure of this field remains fragmented. This study conducts a comprehensive bibliometric analysis to map the evolution, thematic clusters, and emerging trends in strategic management within the digital era. Using Scopus database covering the period 2010–2026, 1,248 peer-reviewed journal articles were analyzed through VOSviewer and Biblioshiny. The analysis reveals an exponential growth in publications, with five dominant thematic clusters: (1) digital transformation and strategy, (2) digital business model innovation, (3) digital and dynamic capabilities, (4) organizational culture and leadership, and (5) sustainability and ESG performance. Influential journals, authors, and countries are identified, along with emerging research fronts including AI adoption, sustainability-driven transformation, and digital refusal. The findings demonstrate a shift from technology-centric perspectives toward holistic approaches integrating culture, leadership, and sustainability. Theoretical contributions include a synthesized framework of the field's intellectual architecture, while practical implications offer strategic roadmaps for managers navigating digital change. Key research gaps concerning SMEs, developing economies, and cross-disciplinary integration are highlighted, providing a future research agenda. This study serves as a foundational reference for scholars and practitioners seeking to understand and advance strategic management in an increasingly digitalized economy.